Determination of the criteria of early caries diagnostics in children of different ethnic groups domiciled in areas biogeochemically deficient in fluorine and iodine* - Klitynska, Oksana V.; Kostenko, Yeugen Y.; Gurando, Viacheslav R. (Journal of Stomatology, 2017)
Aim of the study. To determine the criteria for early diagnosis of carious lesions in children of different ethnic groups permanently exposed to conditions of fluorine and iodine deficiency. Materials and methods. Microbial environment, biochemical parameters and immunological status of saliva in 146 children aged 3-8 years were determined. The study subjects belonged to different ethnic groups. Statistical evaluation of the results was conducted. Results. Dependences of biochemical parameters of microbial flora and local immune characteristics of saliva were determined. Correlation of dependence between pH of saliva, content of ionized calcium and alkaline phosphatase of Ck = 0.825, p<0.01 was also determined. Direct correlation dependence between pH and phosphorus content in the saliva from Ck = -0.876, p <0.01 has been proven, which shows the inverse correlation dependence of intensity of caries and pH of saliva Ck = -0.09, p<0.01. Conclusions. The following correlation dependences have been proven: direct – between pH and phosphorus content; inverse – between pH ionized calcium content and alkaline phosphatase; between the intensity of caries and pH; linear – between the concentration of Streptococcus sobrinus and intensity of caries; exponential – between sIgA concentration and Streptococcus sobrinus; microflora and pH, alkaline phosphatase and intensity of caries.